(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Comparing the relationship between people’s tobacco use and social factors. Subjects and Methods: Cross-sectional design analyzed over 2,400 samples equally divided between men and women, urban and rural areas with a systematic random sampling method collected using quantitative interview questions. Results: The rate of tobacco use in men (29.8%) exceeds that of women (0.8%), more than 47.3 times (24.7-89.6; p < 0.001), group 25 -44 years old (16.35%) and 45-64 years old (19.5%) are respectively 4.3 times (p < 0.01) and 5.2 times (p < 0.01) higher than those aged 15 -24 years old (4.19%); insignificant difference (p > 0.05) between urban (15.1%) and rural (15.6%); The tendency to use less as education increases, especially in university groups; Housewives, students, and retirees have a higher usage rate than office workers with p < 0.01, the difference between freelancers is not significant (p > 0.05). Conclusions: Tobacco use in Binh Duong is lower than the whole country and some neighboring provinces and cities, but it is still concentrated in men (29.8%).